IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN (PNPM-MP) DI DESA SUNGAI BAKAU BESAR LAUT KECAMATAN SUNGAI PINYUH KABUPATEN PONTIANAK - Aziz Febriadinata E.42009012 (FISIP Universitas Tanjungpura Pontianak, 2022)
The purpose of this skripsi is want to know how the process and the obstacle in the PNPM-MP implementation especially in Simpan Pinjam Perempuan (SPP) program in Sungai Bakau Besar Laut village Sungai Pinyuh subdistrict. The title of this skripsi based on the problems of people or groups who didn’t return the money that they lend through the SPP Program.This research using descriptive research with qualitative rapproachement. The data accumulation instrument and the technique of this research are interview and observation guidance to get the complete data. This research show us that PNPM-MP implementation especially SPP program in Sungai Bakau Besar Laut village Sungai Pinyuh subdistrict is good enough, but there still problems in people’s group who lend the SPP’s program money, and also people haven’t involved yet in the determining activity phase and evaluation activity. The conclusion in this research are the implementor must take an extra control of people’s group who lend the SPP’s program money and also people need to involved in determining and evaluation activity. Keyword : PNPM-MP, Simpan Pinjam Perempuan (SPP).